2001
DOI: 10.1002/1521-4141(200103)31:3<687::aid-immu687>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration and tolerance factor of the human placenta induces IL-10 production

Abstract: Regeneration and tolerance factor (RTF) was originally identified in the placenta of mice and the isolated protein shown to have suppressive effects. In these studies, the gene cloned from thymus tissue was mapped to human chromosome 12. The role of recombinant RTF on cytokines was examined. In addition, we examined the human placenta by immunohistochemistry for RTF expression. RTF was expressed at the peripheral layer of cytotrophoblast in 7-9-week-old placentas. Using the RTF gene sequence, a recombinant pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Earlier studies associated a number of immunological effects with a2V expression (20,21) as well as with the recombinantly expressed peptide (10). In similar experiments, MDA cocultured with PBMCs induced the most IL-1b compared with the other cell lines; this correlated with the relatively high a2V expression in MDA cells (Fig.…”
Section: A2v-atpase Utilizes Microvesicles In Il-1b Inductionmentioning
confidence: 99%
“…Earlier studies associated a number of immunological effects with a2V expression (20,21) as well as with the recombinantly expressed peptide (10). In similar experiments, MDA cocultured with PBMCs induced the most IL-1b compared with the other cell lines; this correlated with the relatively high a2V expression in MDA cells (Fig.…”
Section: A2v-atpase Utilizes Microvesicles In Il-1b Inductionmentioning
confidence: 99%
“…We tested mouse sperm for the presence of an important immune regulatory molecule a2V and studied its possible immune-regulatory role during capacitation and early embryonic development. Earlier studies demonstrated that a2V is one of the first molecules expressed in pregnancy that has regulatory effects on the maternal immune response (Lee et al 2001). Sun-Wada et al (2002) have previously reported that a2V was expressed in mature sperm.…”
Section: Introductionmentioning
confidence: 99%
“…There are already known examples of proteins like the regeneration and tolerance factor (RTF) or the oncofoetal protein 5T4 that are expressed in pregnancy tissues as well as in malignantly transformed cells. [7][8][9][10] RTF, similarly to secreted PIBF, exerts an immunosuppressive activity and is expressed during pregnancy by the placenta. 7 Here we present evidence that tumor cells overexpress PIBF relative to normal tissues.…”
mentioning
confidence: 99%
“…[7][8][9][10] RTF, similarly to secreted PIBF, exerts an immunosuppressive activity and is expressed during pregnancy by the placenta. 7 Here we present evidence that tumor cells overexpress PIBF relative to normal tissues. We also demonstrate that different forms of the molecule are generated by alternative mRNA splicing both in normal and malignant cells.…”
mentioning
confidence: 99%